Algae and Polyunsaturated Fatty Acids - Lundquist, Louise (SLU/Department of Molecular Sciences, 2019)
The human body cannot produce enough amounts of long chain polyunsaturated fatty acids (LC-PUFA), on its own, to sustain the biological functions they have. Consuming essential fatty acids is fundamental for well-functioning bodily processes. The essential fatty acids are linoleic acid (LA) and alpha-linolenic acid (ALA). ALA is the precursor to the LC-PUFAs eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA). The metabolism of EPA and DHA in the human body is very limited and it is therefore important to have these fatty acids in our diet. The essential fatty acids can be found in some nuts, seeds and vegetable oils, they are most prominent in canola oil and linseed oil. EPA and DHA cannot be found in nuts, seeds or vegetable oils but are instead found in algae and fish. ALA, EPA, and DHA are categorised as omega-3 fatty acids. Omega-3 fatty acids have an important role in the cell membrane and in retinal tissue. The omega-3 makes the cell membrane fluid and flexible, facilitates the cellular functions and cell signals. EPA is a precursor for the hormone like biochemical substances called eicosanoids. Eicosanoids help aid multiple bodily functions, such as immune functions and inflammatory responses as well as blood pressure regulations and muscle activity. The health benefits of consuming PUFAs are many. They have shown to aid both mental and cardiovascular health. Visual functions have shown risks of being compromised when PUFAs were limited during the infant years. In algae, EPA and DHA are maintaining the photosynthetic functions and may aid cell signalling. Algae have been utilized for over thousands of years. Asians have been the primary consumers, but the consumption of algae is spreading all over the world. Algae are the base, the lowest trophic level, in the aquatic food chain. In modern day they are primarily used as food, but they are also used as biofuel and to purify waste waters. Not all algae are high producers of PUFAs, the most common ones, nori, spirulina etc., are richer in protein and nutrients. The Schizochytrium spp are microalgal species rich in DHA. Phaeodactylum tricornutum and Odontella aurita are two microalgae rich in EPA. The aim of this literature study was to introduce PUFAs and their biological functions. The study also covers the role algae have in the production of EPA and DHA.